Akulturasi Budaya Arsitektur Rumah Adat Kebaya pada Museum Sumpah Pemuda - Michel Dio Susanto; Josephine Roosandriantini (Jurnal Malige Arsitektur, 2020)
Indonesia is a country that is rich in culture and ethnicity, the diversity of traditional houses is one of the nation's wealth. The traditional house of the Betawi tribe, which is commonly called the Kebaya house, has a gable that is folded and leads to the kebaya. The entry of European elements into Indonesia had an impact on the Architectural Style and began to develop Colonial architecture in Indonesia. Colonial architecture is an architectural style that developed in Europe at that time and was adapted to the climate and material climate in Indonesia, to obtain a new form that changed shape in Europe. Thus, there is a mixture of immigrant culture and local culture in a form of architecture called architectural acculturation. Architectural acculturation can be seen in the physical form of the Youth Pledge Museum, which gets a mixture of colonial architecture with the architecture of the Kebaya house. The purpose of this research is to show one of the efforts to more harmonize the archipelago and colonialism.